On demand electrochemical release of drugs from porous reduced graphene oxide modified flexible electrodes - Boulahneche, Samia; Jijie, Roxana; Barras, Alexandre; Chekin, Fereshteh; Singh, Santosh K.; Bouckaert, Julie; Medjram, Mohamed Salah; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
Despite the advantages of an electrochemical control for drug release, only a handful of electrochemical-based release systems have been developed so far. We report herein on the development of an electrochemically activatable platform for on-demand delivery of drugs. It is based on flexible gold thin film electrodes coated with porous reduced graphene oxide (prGO) nanosheets onto which the drug of interest has been integrated beforehand. Two different drugs are investigated here: ondansetron hydrochloride (ODS), a selective 5-HT3 receptor antagonist used for preventing nausea and vomiting caused by chemotherapy and radiotherapy, and ampicillin (AMP), an antibiotic to prevent and treat a number of bacterial infections such as respiratory tract infections, urinary tract infections, and meningitis. In the case of ODS, application of a negative potential bias of -0.8 V results in a sustained slow ODS release with an ODS flux of 47 mu g cm(-2) h(-1). In the case of AMP, we show that polyethyleneimine modified prGO (prGO/PEI) is an extremely efficient matrix. Upon the application of +0.8 V, 24% of AMP could be released from the electrical interface in a time span of 2 h. The released AMP kept its antibacterial activity as demonstrated by antimicrobial tests. These examples illustrate the major benefits of the developed approach for biomedical applications.

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. part 1: lysozyme aggregation at pH 2 and 7.4 - Vasilescu, Alina; Boulahneche, Samia; Chekin, Fereshteh; Gaspar, Szilveszter; Medjram, Mohamed Salah; Diagne, Abdou Aziz; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2017)
Protein instability due to misfolding and aggregation is of big concern for protein based therapeutics because it impacts the bioavailability and immunogenicity of such drugs. The development of simple and cost-effective methods for the analysis of pharmaceutical formulations, indicating the presence or absence of protein aggregates, is consequently of high importance. This work proposes a novel electrochemical interface based on porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) allowing for the early and sensitive identification of protein aggregation by following the change in the oxidative current of the proteins. The novelty of this work lies in the exploration of the ability of GC/prGO interfaces to capture different aggregation behaviors. Lysozyme is used as a model to follow by electrochemistry its aggregation at two pH values, pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Comparing the oxidation peak of lysozyme by differential pulse voltammetry (DPV) for different electrode architectures allowed validating the higher sensitivity of the GC/prGO interface versus bare glassy electrodes or electrodes coated with non-porous reduced graphene oxide. Parallel experiments were performed by fluorescence with thioflavin T, size exclusion chromatography and Atomic Force Microscopy (AFM) imaging. These tests further highlighted the usefulness of GC/prGO electrode to visualize in a fast and reliable manner the changes in the protein structure and the differences between the processes occurring at pH 2 and pH 7.4. In particular, the ability to emphasize changes related to the first steps in aggregation that could be indicative of the aggregation course, recommend the GC/prGO electrode in combination with DPV as a new analytical tool for aggregation studies of biopharmaceuticals. Part 2 of this work will demonstrate later the utility of this approach for the analysis of a fast acting injectable human insulin formulation, Humulin R, used for diabetes treatment as well as for calcitonin. (C) 2017 Elsevier Ltd. All rights reserved.

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 2: Application to the analysis of calcitonin containing pharmaceutical formulation - Vasilescu, Alina; Ye, Ran; Boulahneche, Samia; Lamraoui, Sabrina; Jijie, Roxana; Medjram, Mohamed Salah; Gaspar, Szilveszter; Singh, Santosh K.; Kurungot, Sreekumar; Melinte, Sorin; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2018)
In part 1 (A. Vasilescu et al., Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 1: Lysozyme aggregation at pH 2 and 7.4 Electrochem. Acta, 254 (2017) 375 -383) we proposed porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) in combination with differential pulse voltammetry as a new analytical tool for aggregation studies of proteins. Lysozyme was used as a model to follow its aggregation by electrochemical means at pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Part 2 of this work widens the scope of this approach by investigating a biopharmaceutical product, as the aggregation of peptide based drugs affects their therapeutic activity and can induce allergic reactions in patients. The salmon polypeptide calcitonin (sCT) was chosen as an example of a bioactive peptide with limited pharmaceutical potential due to a tendency to form cytotoxic aggregates and amyloid fibrils. For practical applications, screen printed electrodes (SPE) and flexible electrodes (FE) modified with polydiallyldimethylammonium (PDDA) and prGO by using the layer-by-layer deposition technique have been developed for the detection of sCT. The results indicate that these electrodes can differentiate between formation of amyloid aggregates of calcitonin (2 mg mL(-1)) in citrate buffer to no aggregation in acetate buffer. It was further demonstrated that these electrodes are able to analyze a pharmaceutical drug product of low potency, Miacalcic (8.3 mu g mL(-1)), where no aggregation was observed. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Calcitonin; Disposable electrodes; Electrochemistry; Porous reduced graphene oxide; Protein aggregation